Consumer behavior and market segmentation for workplace safety consultants of small business - Rodrigues, Tonny Kerley de Alencar (2015)
The research aims to use marketing principles to address the proper techniques that can be usefully applied by security consultant’s work for small businesses. In turn, this research can be classified as qualitative, descriptive where were analyzed information’s contained the Work Accident Statistical Year book also can be characterized how descriptive, since it describes  the marketing activities to be used with small businesses, and is a cross-sectional study involving several cases in which data were collected in a single chronological step. The literature was developed using marketing authors and Work safety. The data were analyzed using the factors that influence consumer behavior Chisnall (1995), the model of the buying decision process described by Kotler (1967), stages of growth proposed by Churchill and Lewis (1983) business, strategic and specific definitions for small businesses described by Rodrigues (2012). It was identified that small businesses have characteristics that are centered around the owner. As a marketing strategy, personal selling can be effective.